2016
DOI: 10.9788/tp2016.3-14en
|View full text |Cite
|
Sign up to set email alerts
|

Families Headed by Lesbian, Gay and Bisexual Individuals: A Systematic Literature Review

Abstract: The aim of the present study was to describe the scientifi c literature on families constituted by lesbian, gay and bisexual individuals, through a systematic review of national and international studies published between 2009 and 2013. The following databases were searched: Scientifi c Electronic Library Online (SciELO), Periódicos Eletrônicos de Psicologia (PePSIC), Literatura Latino-Americana e do Caribe em Ciências da Saúde (LILACS), Index Psi, PsyINFO and PUBMED. After the application of inclusion and exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 46 publications
(61 reference statements)
0
2
0
Order By: Relevance
“…Studies on lesbian mother families found that exhaustion and parental stress were lower for these families since parental responsibilities were equally shared 6,16 . This positive effect was evident in other studies that compared lesbian mother families with gay, bisexual, and heterosexual parent families 18,[22][23][24] . This finding may be explained with reference to the absence of heteronormative codes in lesbian mother families.…”
Section: Positive Experiencesmentioning
confidence: 66%
See 1 more Smart Citation
“…Studies on lesbian mother families found that exhaustion and parental stress were lower for these families since parental responsibilities were equally shared 6,16 . This positive effect was evident in other studies that compared lesbian mother families with gay, bisexual, and heterosexual parent families 18,[22][23][24] . This finding may be explained with reference to the absence of heteronormative codes in lesbian mother families.…”
Section: Positive Experiencesmentioning
confidence: 66%
“…Although participants in some of the studies expressed that the society was more tolerant of LGBT+ parents, the majority of studies reported that social discrimination continued even after parenthood 7,11,[21][22][23][24][25] . Problems of LGBT+ individuals in work life included precariousness, discrimination, and being unable to benefit from the rights of heterosexual employees, such as maternity and paternity leave, breastfeeding leave, unpaid leave, or flexibility in working hours 7,19,21 .…”
Section: Negative Experiencesmentioning
confidence: 99%